Ruido de disparo - Betancourt Uscátegui, Alvaro (Ingeniería, 1999)
Two topics will always be searching and treatment. One, the information and the other the noise: In the first one, the objetive will be to maximize, while in the other is to minimize it, in both cases the purpose is to obtain the better results. Intrinsic noise was separated in two major categories: shot noise that is the purpose of this paper, and, thermal noise. The physical origins of theses two categories are distinct, but the structures of noise waveform are similar.